Source of Benzene, Characteristics and Hemoglobin Levels of AHASS Mechanical Workers at Kediri City - Erini Meilina Bestari (Universitas Airlangga, 2019)
Benzene exposure to mechanic workers came from contact with gasoline and oil. Source of exposure benzene is entering the human body through breathing, skin, and mouth. Then it would be distributed into the bone marrow. So, the cell processes in the blood were disrupted. The purpose of this study was to determine the source of benzene, characteristics and hemoglobin levels of mechanical workers. This research was an observational study, using a cross-sectional design. The sample in this study were 20 mechanical workers, taken randomly by simple random sampling. Blood samples were taken to measure hemoglobin levels and a questionnaire to see mechanical characteristics, such as age, length of work, years of service, a habit of washing hands with gasoline, smoke habits, and body armor. Data analyzed descriptively. There was a source of benzene in the work environment such as gasoline, motor vehicle fumes, gasoline vapor, oil, used oil, and majun. Characteristics of the mechanical workers have the habit of washing hands with gasoline after contact with oil by 75% and all mechanical workers have normal hemoglobin levels. Mechanics are advised to wash their hands with soap and water after each work without using gasoline, and as well as holding socialization related to occupational health and safety.